Sudden stops and reserve accumulation in the presence of international liquidity risk - Lutz, Flora,Zessner-Spitzenberg, Leopold (Verein für Socialpolitik, 2020)
We propose a small open economy model where agents borrow internationally and invest in liquid foreign assets to insure against liquidity shocks, which temporarily shut out the economy of short-term credit markets. Due to the presence of a pecuniary externality individual agents borrow too much and hold too little liquid assets relative to a social planner. This inefficiency rationalizes macroprudential policy interventions in the form of reserve accumulation at the central bank coupled with a tax on foreign borrowing. Unless combined with other measures, a tax on foreign borrowing is detrimental to welfare; it reduces agents' incentives to invest in liquid assets and thereby increases financial instability. Our model can quantitatively match the simultaneous depreciation of the exchange rate and contractions in output, gross trade ows, foreign liabilities and foreign reserves during sudden stop episodes.
10419/224520
Keywords: Kongressbeitrag; Graue Literatur; international reserves; sudden stops; liquidity; macroprudential policy; pecuniary externalities